ANALYSIS OF THE REGIONAL LEGAL BASE REGULATING DEVELOPMENT AND IMPLEMENTATION OF PUBLIC PROGRAMS - Elena I. Dobrolyubova; Elena N. Klochkova (Статистика и экономика, 2016)
The budget legislation stipulates that starting from the budget cycle of 2016, all Russian regions should form their budgets based on public (state) programs. The article presents the results of the analysis of regional legal acts and regulations aimed at assessing readiness on the part of the regions to implement program budgeting practices and identifying regional specifics of such regulation. The analysis allowed to identify regional approaches to setting procedures and regulating the contents of regional public programs, evaluate the relations between program development and regional budget planning procedures, define specific approaches to monitoring and evaluating performance of regional public programs.